Transcriptome Dynamics in Mango Fruit Peel Reveals Mechanisms of Chilling Stress - Sivankalyani, Velu; Sela, Noa; Feygenberg, Oleg; Zemach, Hanita; Maurer, Dalia; Alkan, Noam (Frontiers in Plant Science, 2016)
Cold storage is considered the most effective method for prolonging fresh produce storage. However, subtropical fruit is sensitive to cold. Symptoms of chilling injury in mango include red and black spots that start from discolored lenticels and develop into pitting. The response of ‘Keitt’ mango fruit to chilling stress was monitored by transcriptomic, physiological and microscopic analyses. Transcriptomic changes in the mango fruit peel were evaluated during optimal (12°C) and suboptimal (5°C) cold storage. Two days of chilling stress upregulated genes involved in the plant stress response, including those encoding transmembrane receptors, calcium-mediated signal transduction, NADPH oxidase, MAP kinases and WRKYs, which can lead to cell death. Indeed, cell death was observed around the discolored lenticels after 19 days of cold storage at 5°C. Localized cell death and cuticular opening in the lumen of discolored lenticels were correlated with increased general decay during shelf-life storage, possibly due to fungal penetration. We also observed increased phenolics accumulation around the discolored lenticels, which was correlated with the biosynthesis of phenylpropanoids that were probably transported from the resin ducts. Increased lipid peroxidation was observed during chilling injury by both the biochemical malondialdehyde method and a new non-destructive luminescent technology, correlated to upregulation of the α-linolenic acid oxidation pathway. Genes involved in sugar metabolism were also induced, possibly to maintain osmotic balance. This analysis provides an in-depth characterization of mango fruit response to chilling stress and could lead to the development of new tools, treatments and strategies to prolong cold storage of subtropical fruit.